Evaluation of a Level I trauma center provider training in patient-centered alcohol brief interventions using the Behavior Change Counseling Index rated by standardized patients. Issue 1 (29th December 2019) - Darnell, Doyanne; Parker, Lea; Engstrom, Allison; Fisher, Dylan; Diteman, Kaylie; Dunn, Christopher
Abstract : Background: Traumatic injury requiring hospitalization is common in the USA and frequently related to alcohol consumption. The American College of Surgeons requires that Level I and II verified trauma centers implement universal alcohol screening and brief intervention for injured patients. We examined whether Level I trauma center provider skill in patient-centered alcohol brief interventions improved after training and whether professional role (eg, nursing, social work) and education were associated with these skills. Methods: We present evaluation data collected as part of training in alcohol brief interventions embedded within a larger clinical trial of a collaborative care intervention targeting posttraumatic stress disorder and related comorbidities. Sixty-five providers from 25 US Level I trauma centers engaged in a 1-day workshop, with 2 hours dedicated to training in patient-centered alcohol brief interventions followed by 6 months of weekly coaching in a collaborative care model. Providers completed standardized patient role-plays prior to and 6 months after the workshop training. The standardized patient actors rated provider quality of alcohol brief interventions immediately after each role-play using the Behavior Change Counseling Index (BECCI), a pragmatic measure designed to assess the quality of behavior change counseling, an adaptation of motivational interviewing suitable for brief healthcare consultations about behavior change. Results: Seventy-two percent of providers completed both standardized patient role-play assessments. A statistically significant improvement in overall BECCI scores ( t (41)=−2.53, p=0.02, Cohen's d =−0.39) was observed among those providers with available pre–post data. Provider professional role was associated with BECCI scores at pre-training ( F (3, 58)=11.25, p<0.01) and post-training ( F (3, 41)=8.10, p<0.01). Discussion: Findings underscore the need for training in patient-centered alcohol brief interventions and suggest that even a modest training helps providers engage in a more patient-centered way during a role-play assessment. Level of evidence: Level V, therapeutic/care management.